1991
DOI: 10.1007/bf00170658
|View full text |Cite
|
Sign up to set email alerts
|

The different use dependences of tocainide and benzocaine are correlated with different effects on sodium channel inactivation

Abstract: To study the mechanism of use dependence, we investigated the influence of 0.5 mM tocainide on the amplitude of sodium currents elicited by membrane depolarizations with standard test pulses in voltage-clamped human myoballs. For comparison, the experiments were also conducted with 1 mM benzocaine, a drug with almost no use dependence. These concentrations were so chosen that without stimulation and at a holding potential of -135 mV, either drug blocked about 50% of the channels (tonic block). With repetitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…lidocaine) produce little tonic and much use-dependent block, but the inverse can also occur (36,37). For example, the neutral LA benzocaine acts almost exclusively through tonic block (38). To avoid the pro-arrhythmic potential of use-dependent Na ϩ channel block in the development of specific therapeutic applications such as pain treatment, it will therefore be important to determine the molecular details of tonic block.…”
Section: Discussionmentioning
confidence: 99%
“…lidocaine) produce little tonic and much use-dependent block, but the inverse can also occur (36,37). For example, the neutral LA benzocaine acts almost exclusively through tonic block (38). To avoid the pro-arrhythmic potential of use-dependent Na ϩ channel block in the development of specific therapeutic applications such as pain treatment, it will therefore be important to determine the molecular details of tonic block.…”
Section: Discussionmentioning
confidence: 99%
“…A parallel increase in lipophilicity and molecular dimension can help reinforce hydrophobic interactions during state-dependent conformational change of the channel vestibule and slow the kinetic to reach a new equilibrium between free and drug-bound channels (Yarov-Yarovoy et al, 2001). In addition, a change in the pK a of the basic amine can in turn contribute to the inactivated and usedependent behavior, on the basis of the state-dependent affinity of protonated amine and drug ability to access to and egress from the receptor (De Luca et al, 1991, 1997aCatterall, 2002;Liu et al, 2003). In this study, we confirmed that the high use-dependent behavior of To5 (Talon et al, 2001) is paralleled by a high estimated pK a value, which slows down Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The asparagine at 434 on D1 (in the skeletal muscle isoform), involved in the stereoselective interaction, can directly establish hydrogen-bonds with the positive charged moiety of LAs during channel inactivation (Nau et al, 1999). A further kinetic analysis of the recovery from inactivation will be pivotal in clarifying the contribution of drug affinity to inactivated state in determining the use-dependent behavior of the test compounds (De Luca et al, 1991, 1997a. However, a preliminary evaluation of the time course of recovery from usedependent block of equieffective concentrations of To5 and Toc showed that the former is only slightly slower in recovering (data not shown), whereas we have shown herein that To5 is surely slower in the development of the use-dependent block, probably in relation to the higher fraction of charged molecule, which hinders a rapid equilibration with the internal receptor site.…”
Section: Discussionmentioning
confidence: 99%
“…In both channel types, however, depolarization increased the block, and steadystate inactivation curves were shifted to more negative values. In this respect, block of TTX-r channels by ambroxol shares similarities with the effects of benzocaine on Na ϩ channels (DeLuca et al, 1991;Baker, 2000). Nevertheless, ambroxol has a much higher (about 10-fold) potency compared with benzocaine.…”
Section: Discussionmentioning
confidence: 99%